Effect of type of emulsifiers and antioxidants on oxidative stability, colour and fatty acid profile of low-fat beef burgers enriched with unsaturated fatty acids and phytosterols - Pennisi Forell, Susana Carolina (2010)
Low-fat beef burgers were formulated using fresh lean meat, 9.9% oleic sunflower oil and 0.1% deodorized fish oil to obtain a product enriched in unsaturated fatty acids. The effect of two emulsifiers (whey proteins or egg white) and natural antioxidants (tocopherols and/or oregano-rosemary), as well as the influence of frozen storage on the oxidative stability, colour, and fatty acid (FA) profile was determined on the cooked products. Whey proteins protected better against oxidation than egg white, and tocopherols demonstrated an adequate antioxidant effect in formulations with egg white. For all the formulations the unsaturated/saturated FA ratio was higher than 5.8, showing a good lipid balance in the products. The consumption of 100 g of the cooked product would provide 6% of the recommended daily intake of phytosterols suggested to decrease cholesterol and the risk of heart disease. Formulated low-fat burgers with preemulsified oils and phytosterols could be considered to be potentially functional foodstuffs.